A master euphonium recital and program notes - Switzer, Trey Alan (Kansas State University, 2023)
This master report focuses on a brief history, analysis, and pedagogy of four essential compositions in euphonium repertoire. The first chapter focuses on Sonata in F Minor T.M.V. 41 by Georg Philip Teleman. It includes a short biography of Georg Philip Teleman, a background on the composition, and a theoretical and pedagogical analysis of the piece. The second chapter focuses on Fantaisie Concertante by Jacques Castéréde. It includes a short biography of Jacques Castéréde, a background on the composition, and a theoretical and pedagogical analysis of the piece. The third chapter focuses on Party Piece by Philip Sparke. It includes a short biography of Philip Sparke, a background on the composition, and a theoretical and pedagogical analysis of the piece. Finally, the fourth chapter focuses on Concertino for Euphonium by Rolf Wilhelm. It includes a short biography of Rolf Wilhelm, a background on the composition, and a theoretical and pedagogical analysis of the piece. These works will be performed as a recital on April 1st, 2023, in All Faiths Chapel, Kansa State University.
Keywords: Euphonium; Master; Program notes; Maxwell; Master report; Switzer